Sweet Sorghum as a Potential Fallow Crop in Sugarcane Farming for Biomethane Production in Queensland, Australia - Divya Joslin Mathias; Thiago Edwiges; Napong Ketsub; Rajinder Singh; Prasad Kaparaju (Energies, 2023)
Biogas from lignocellulosic feedstock is a promising energy source for decentralized renewable electricity, heat, and/or vehicle fuel generation. However, the selection of a suitable energy crop should be based on several factors such as biomass yields and characteristics or biogas yields and economic returns if used in biorefineries. Furthermore, the food-to-fuel conflict for the use of a specific energy crop must be mitigated through smart cropping techniques. In this study, the potential use of sweet sorghum as an energy crop grown during the fallow periods of sugarcane cultivation was evaluated. Nine sweet sorghum cultivars were grown on sandy loam soil during September 2020 in North Queensland, Australia. The overall results showed that the crop maturity had a profound influence on chemical composition and biomass yields. Further, the total insoluble and soluble sugar yields varied among the tested cultivars and were dependent on plant height and chemical composition. The biomass yields ranged from 46.9 to 82.3 tonnes/hectare (t/ha) in terms of the wet weight (w/w) of the tested cultivars, with the SE-81 cultivar registering the highest biomass yield per hectare. The gross energy production was determined based on the chemical composition and methane yields. Biochemical methane potential (BMP) studies in batch experiments at 37 °C showed that methane yields of 175 to 227.91 NmL CH4/gVSadded were obtained from the tested cultivars. The maximum methane yield of 227.91 NmL CH4/gVSadded was obtained for cultivar SE-35. However, SE-81 produced the highest methane yields on a per hectare basis (3059.18 Nm3 CH4/ha). This is equivalent to a gross energy value of 761.74 MWh/year or compressed biomethane (BioCNG) as a vehicle fuel sufficient for 95 passenger cars travelling at 10,000 km per annum. Overall, this study demonstrated that sweet sorghum is a potential energy crop for biogas production that could be cultivated during the fallow period of sugarcane cultivation in Queensland.